2009
DOI: 10.1515/cclm.2009.162
|View full text |Cite
|
Sign up to set email alerts
|

Proficiency test of plasma free and total metanephrines: report from a study group

Abstract: Keywords: pilot study; plasma free metanephrines; plasma total metanephrines; proficiency testing.The diagnosis of pheochromocytoma is based on the quantitation of O-methylated metabolites of catecholamines (1, 2). Several studies have reported high sensitivity of free metanephrines in plasma for assessing the presence of tumour (1). Measurement of plasma total metanephrines (plasma freeqplasma sulphoconjugated metanephrines) has also been proposed as a diagnostically sensitive assay (3). Therefore, an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
(11 reference statements)
0
8
0
2
Order By: Relevance
“…For normetanephrine, intra‐assay and inter‐assay coefficients of variation of 15% (for 155·5 ± 5·4 ng/l) and 7–17% (7% for 882·4 ± 15·1 ng/l, 17% for 90·3 ± 3·8 ng/l), respectively, were found. Whereas a recent publication showed that the immunoassay from LDN had inter‐assay coefficients of variation of up to 31%, 14 the generation of assays provided for the current study demonstrated better precision. Apparently, for unknown reasons, specific production cycles of an older assay generation had larger variability especially in the lower range.…”
Section: Methodsmentioning
confidence: 64%
“…For normetanephrine, intra‐assay and inter‐assay coefficients of variation of 15% (for 155·5 ± 5·4 ng/l) and 7–17% (7% for 882·4 ± 15·1 ng/l, 17% for 90·3 ± 3·8 ng/l), respectively, were found. Whereas a recent publication showed that the immunoassay from LDN had inter‐assay coefficients of variation of up to 31%, 14 the generation of assays provided for the current study demonstrated better precision. Apparently, for unknown reasons, specific production cycles of an older assay generation had larger variability especially in the lower range.…”
Section: Methodsmentioning
confidence: 64%
“…Interestingly, our healthy subjects had lower plasma norepinephrine and total metanephrines, plasma free and urinary metanephrine than the controls (average differences 24-43%, P!0.05). This underscores the importance of establishing local reference values for such biochemical parameters until inter-laboratory standardization is achieved (19).…”
Section: Biochemical Resultsmentioning
confidence: 99%
“…The negative bias of EIA measurements of plasma MNs was initially suggested from results of an inter-laboratory quality assurance program that utilized pooled lyophilized plasma spiked with commercially available racemic enantiomers of MNs in the first series (11), and plasma spiked with natural L-enantiomers derived from urine was used in a subsequent series (12). The distinction is important, as the natural L-enantiomers of MN are the forms targeted by immunoassays (5).…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these studies compared the immunoassay with either LC-ECD or LC-MS/MS. First reports from inter-laboratory proficiency programs suggest that immunoassays may be less precise and accurate than both other methods (11,12). Suggestions that immunoassays show a negative bias, leading to potential missed diagnoses, were further suggested by two other studies (13,14).…”
Section: Introductionmentioning
confidence: 99%